Efficacy of Retrobulbar versus Topical Anesthesia in Cataract Surgery - Muhammad Sajid Munir, Muhammad Arshad, Shahid Nazir, Nusrat Sharif, Mariam Zakia Chaudhari, Rizwanullah, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To monitor the effect of retrobulbar versus topical anesthesia in cataract surgery patients by comparing different parameters such as: intraocular pressure akinesia and analgesia parameters. Study type: Interventional case series. Place and duration of study: Department of Ophthalmology, Niazi Medical & Dental College Sargodha from 1st October 2020 to 31st October 2021. Methodology: One hundred patients who underwent cataract surgery were enrolled. Study participants were divided into two groups and each group contain fifty 50 participants. Group one give retrobulbar block and group two treated by topical anesthesia. Complete ocular and systematic examinations and relevant examinations like clotting time, blood pressure, blood sugar, complete blood examination and bleeding time were done before starting the surgery. Results: 80% were males and 20% were females. During topical local anesthesia, 47(94%) patients experienced pain free surgery whereas in retrobulbar anesthesia, only 38(76%) patients experienced pain free surgery. In retrobulbar anesthesia group, complete akinesia was observed in 25(50%) patients. In retrobulbar group, significant increase in intraocular pressure was noted 41(82%) upto 30 mmHg after the administration of local anesthesia as compared to topical anesthesia group. Conclusion: Topical anesthesia is more safe and effective approach for cataract patients in contrast to retrobulbar group. It prevents many life and sight threatening implications like globe perforation and brain stem anesthesia.